ATTENDANCE SYSTEM FOR BATUBARA DISTRICT GOVERNMENT EMPLOYEES USING WEB TECHNOLOGY - Ade Kurniawan Hasibuan; Hafni Nasution; Muhammad Donni Lesmana Siahaan (Bahasa Indonesia, 2026)
The attendance system is an important component in employee performance monitoring, particularly in government agencies where data accuracy and timeliness are crucial. In Batubara District Government, the conventional attendance recording process often encounters issues such as delayed input, data manipulation, and ineffective reporting. This research aims to develop a web-based attendance system to improve efficiency, accuracy, and transparency in recording employee attendance. The system was built through several stages including problem identification, literature review, data collection, system analysis, design, implementation, and testing. The resulting application allows real-time attendance recording through web-based access, featuring user authentication, attendance logging, employee data management, and automated reporting. Testing using the black box method indicated all functions operated correctly, and user feedback confirmed increased convenience and transparency. Despite challenges related to internet dependency and user adaptation, the system shows great potential in supporting modern and accountable human resource management practices in regional government.